2014
DOI: 10.1128/iai.01041-13
|View full text |Cite
|
Sign up to set email alerts
|

MBL2Variations and Malaria Susceptibility in Indian Populations

Abstract: The frequencies of low MBL haplotypes were significantly higher in severe malaria (14.2%) compared to mild malaria (7.9%) and asymptomatic (3.8%). The MBL2*LYPA haplotypes confer protection, whereas MBL2*LXPA increases the malaria risk. Our findings in Indian populations demonstrate that MBL2 functional variants are strongly associated with malaria and infection severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…In order to avoid identifying allelic associations that were actually due to other genetic variations associated with race, we excluded study participants who did not self-report being Caucasian; and thus additional research will be required for establishing severity correlates in other populations. We were concerned that variation in genes such as MBL2 that show race-associated differences in allele frequency and that have been shown to be associated with infection severity could confound our results (37-39). Self-reported ancestry can be imperfect and future research can potentially include genetic assessment of the background of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…In order to avoid identifying allelic associations that were actually due to other genetic variations associated with race, we excluded study participants who did not self-report being Caucasian; and thus additional research will be required for establishing severity correlates in other populations. We were concerned that variation in genes such as MBL2 that show race-associated differences in allele frequency and that have been shown to be associated with infection severity could confound our results (37-39). Self-reported ancestry can be imperfect and future research can potentially include genetic assessment of the background of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, three non-synonymous [18]. Lectin complement proteins have been associated with many infectious diseases including intra and extracellular infections [22][23][24][25]. Our earlier study has shown that, another analogous lectin complement protein ficolin-2 was associated with occurrence of VL [26].…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…The MBL2*LYQA haplotype is associated with higher MBL expression and reduced risk in severe malaria patients [45]. The MBL2*LYPA haplotype was associated to be a risk factor in a study on Brazilian patients with leprosy caused by another intracellular pathogen [46].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although the role of MBL2 genetic variants has been investigated widely in different diseases, infections, and pathophysiological conditions [as a recent examples see Takahashi, 2011;Heitzeneder et al, 2012;Carvalho et al, 2013;Evans-Osses et al, 2013;Lu et al, 2013;Swierzko et al, 2013;Wan et al, 2013;Ingels et al, 2014;Jha et al, 2014], no previous studies have investigated the possible correlation between MBL2 polymorphisms and atypical squamous cells of undetermined significance susceptibility.…”
Section: Discussionmentioning
confidence: 99%